Sosialisasi Sustainable Development Goals (SDGs) Desa di Desa Ujung Pandaran Kecamatan Teluk Sampit Kabupaten Kotawaringin Timur Kalimantan Tengah - Sri Mujiarti Ulfah; Syamsuri; Marvy Ferdian Agusta Sahay; Ummu Habibah Gaffar; Nadya Grestyana; Edward Melio Bertho; Puput Ratnasari (Jurnal Pengabdian Kampus, 2024)
Development in rural areas is still a chore that must be completed, in tandem with capacity building activities and community empowerment in rural areas so that they are empowered and strengthen their economic activities which will have an impact on their welfare. SDGs Desa is a derivative program from the SDGs issued by the United Nations. SDGs Desa is a policy to accelerate the achievement of the Sustainable Development Goals which have 18 goals. The village government is expected to be able to make the right program as evidenced by the commitment to use village funds for development in the village. In addition, the village government needs to build synergies with the community so that the existence of village communities is not an object of development but also a subject, so that the existence of village communities is able to contribute actively to support Village SDGs. One of them is the village of Ujung Pandaran.